MUET workshop 2016 - Ch’ng, Looi Chin; Chan, Ai Nyet (Universiti Teknologi MARA, Sarawak, 2016)
The objectives were to expose students to the syllabus and format of MUET as well as provide guidelines, strategies and hands-on practices for MUET. With this workshop, it was hoped that students could score higher bands in the test. This one-day workshop touched on the marking criteria to assist students to score better in each component of the test namely Reading, Writing, Speaking and Listening. They were taught some effective answering techniques for each component too.